Konsep Masa Iddah Perempuan yang Ditinggal Mati Suami - Juwairiah; Gina, Miftahul; Azkiya, Muhammad Rifqi (Sharia Journal and Education Center Publishing, 2024)
Abstract ‘Iddah is intended as a calculation or something that is counted. Calculating ‘iddah can be done either by counting the menstrual cycles or by counting the period of purity for a woman. ‘Iddah is the waiting period for a woman to remarry after the dissolution of a marriage, whether due to divorce or the death of the spouse. The purpose is to determine the condition of her womb and to reconsider reconciliation with her husband. The method used in this research is a literature study, primarily sourced from the book written by Sheikh Muhammad Arsyad Al-Banjary titled “Kitabun Nikah”. The results of this study indicate that the ‘iddah for a woman who is not pregnant is four months and ten days. Keywords: 'Iddah Period, Women, Husband's Death Abstrak ‘Iddah dimaksudkan sebagai perhitungan atau sesuatu yang dihitung. Menghitung ‘iddah baik dengan menghitung dari haid ataupun menghitung dari sucinya seorang perempuan. Iddah adalah masa menunggu bagi seorang perempuan untuk melakukan perkawinan setelah terjadinya perkawinan, dan terjadi perpisahan yang disebabkan cerai hidup atau cerai mati. Dengan tujuan untuk mengetahui keadaan rahimnya dan untuk memikirkan ulang untuk bisa rujuk dengan suaminya. Metode yang digunakan dalam penelitian ini adalah studi kepustakaan, yang bersumber utama dari kitab karangan Syeikh Muhammad Arsyad Al-Banjary yang berjudul “Kitabun Nikah”. Hasil penelitian ini menunjukkan bahwa ‘iddah bagi perempuan yang tidak hamil adalah empat bulan sepuluh hari. Kata kunci : Masa ‘Iddah, Perempuan, Mati Suami